A study on noise pollution at school / Norasyikin Ismail - Ismail, Norasyikin (2010)
Noise is defined as unwanted sound. Environmental noise consists of all the unwanted sounds in our communities except that which originates in the workplace. Environmental noise pollution, a form of air pollution, is a threat to health and well- being. It is more severe and widespread than ever before, and it will continue to increase in magnitude and severity because of population growth, urbanization, and the associated growth in the use of increasingly powerful, varied and highly mobile sources of noise. It will also continue to grow because of sustained growth in highway, rail, air traffic, new construction, and other, which remain major sources of environmental noise. The potential health effects of noise pollution are numerous, pervasive, persistent and medically and socially significant. Noise produces direct and cumulative adverse effects that impair health and that degrade residential, social, working and learning environments with corresponding real ( economic) and intangible ( well-being ) losses. It interferes with sleep, concentration, communication and recreation. The aim of enlightened governmental controls should be to protect citizens from the adverse effects of airborne pollution including those produced by noise. People have the right to choose the nature of their acoustical environmental it should not be imposed by others.